Contribution beverages for hydration before, during and after physical activity in university students - Carla Andreia Lima Ferreira; José Augusto Rodrigues dos Santos; Luiza Kent-Smith; Inês Sofia Morales Salcedo (Desafio Singular, 2008)
Introduction: intake of liquids before, during and after physical activity has beneficial effects on body hydration of physically active individuals, preventing dehydration and increasing the physical capacity. Objectives: to evaluate the knowledge, contribution and consumption beverages before, during and after physical activity in a group of physically active university students, to evaluate the body composition, physical activity and energy expenditure during weekly physical activity. Methodology: we carried out a survey of 348 students, 140 female and 208 male, currently attending from the 1st to the 4th year of the Faculty of Sport of the University of Porto. They were appraised through a specific questionnaire and anthropometrical evaluation. Statistical treatment was performed using SPSS, version 13.0 for Windows and Microsoft Excel 2003 for p<0.05. Results: It was verified that 1st and 2nd year students practice and spend more calories with physical activity in a typical week. About 95% of the students consider it necessary to consume beverages before, during and after physical activity. Hydration is mentioned more often by students as justification for the need and consumption of beverages, before, during and after physical activity. Of the students that practiced physical activity, about 85% consume beverages before, during and after physical activity, in at least one sport modality practiced. Discussion: Hydration is for the surveyed students the main justification for the need and consumption of beverages before, during and after physical activity. Water is the students' preferred beverage for consumption during physical activity.